Building Global Capacity to Conduct Pathology-Based Postmortem Examination: Establishing a New Training Hub for Minimally Invasive Tissue Sampling. (15th December 2021) - Paganelli, Christina R; Parlberg, Lindsay; Goco, Norman J; Ritter, Jana M; Martines, Roosecelis B; Zaki, Sherif R; Walong, Edwin; Ochieng, Washington; Inyangala, Dennis; Barake, Walter; Wachiury, Cyrus; Rakislova, Natalia; et al.
Abstract: Background: Minimally invasive tissue sampling (MITS), an alternative to complete diagnostic autopsy, is a pathology-based postmortem examination that has been validated in low- and middle-income countries (LMICs) and can provide accurate cause of death information when used with other data. The MITS Surveillance Alliance was established in 2017 with the goal to expand MITS globally by increasing training capacity, accessibility, and availability in LMICs. Between January 2019 and May 2020, the MITS Surveillance Alliance convened a multidisciplinary team of technical advisors to attain this goal. Methods: This article describes the process used to develop criteria and identify an optimal location for a MITS training hub, establish a cadre of LMIC-based trainers, refine standardized MITS sample collection protocols, develop a training program, and release a telepathology platform for quality assessment of MITS histological samples. Results: Results include the creation of a training hub and curriculum, with a total of 9 pathologists and technicians trained as part of the training of the trainers. Those trainers trained 15 participants from seven MITS projects representing 6 LMICs trained in MITS sample collection. The 15 participants have gone on to train more than 50 project-level staff in MITS sample collection. Conclusions: Lessons learned include an appreciation for using an iterative process for establishing standardized procedures, creating opportunities for all stakeholders to deliver critical feedback, and highlighting the importance of complementing in-person trainings with ongoing technical assistance.